PENGARUH MEDIA KONKRET TERHADAP HASIL BELAJAR MATEMATIKA KELAS III SEKOLAH DASAR - Defti Frawiyandani; K. Y. Margiati; Tahmid Sabri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe problem in this research was "is there any influence of the use of concrete materials resolution on media issues related to money towards learning outcomes of students in class III SDN 66 Pontianak City?". This research aimed to analyze whether there is influence of concrete media use on the troubleshooting material related to the money against the learning outcomes of students in class III SDN 66 Pontianak town. The population of the whole student consisted of two classes, namely class III A and III B with a total of 55 people. The selection of the sample was randomly done with doing the draw and retrieved samples of research i.e. class III A (experimental classes) that consists of 28 students and class III B (grade control) which consists of 27 students. Statistical calculation based on the average of the results of learning tests end of class III A (experimental) of 69 and an average learning outcomes tests end of class III B (control) of 56.02 retrieved thitung amounted to 4.132 and ttabel α = 5% (with dk = 28 + 27-2 = 53) of 1.676 which means tcalculated (4.132) > ttable (1.676), the Ha received, this proves there is a significant difference of two average student learning outcomes, between a group of students who are taught using concrete, media and groups of students taught by using media images. Based on the calculation of effect size (ES) obtained ES = 1.09 (criteria very high) this means the use of concrete materials resolution on media issues related to money gave very high influence against the learning outcomes of students in class III SDN 66 The City Of Pontianak. Keywords: Effect, Conrete Media in Mathematic, Results.